COMMUNITY EMPOWERMENT IN MANAGING THE POTENTIAL OF MINING MATERIALS - Asmiani, Nur; Jafar, Nurliah; Nurhawaisyah, Sitti Ratmi; Manik, Nijushiho (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2024)
Pattappa Village is a village that has the potential for minerals. However, in developing its potential, residents tend to ignore it because they do not know how to manage it. Residents only know that to manage it, they must attract investors. The uniqueness of the mineral excavation potential can be encouraged from a tourism perspective. This can ensure sustainability compared to mining, which has a management life. Community empowerment activities aim to provide an understanding of the potential of mineral excavation-based tourism owned by the village. The implementation is by conducting socialization, filling out questionnaires, and discussing the evaluation of questionnaire results. The activity results showed a paradigm shift in villagers’ development of tourism potential. Residents have the awareness to manage the potential of minerals in geotourism.